GIS-basedland suitability analysis of sustainable hillside development - Chandio, I.A. (Elsevier Ltd, 2014)
Hillsides have encroached for development because of increasing scarcity of flat land. This would potentially create serious environmental issues such as unstable slope collapse. A GIS-based Multi-criteria Decision Analysis (MCDA) was used for land suitability analysis of hillside development. However, an Analytic Hierarchy Process (AHP) as a MCDA approach was used to weight the suitability criteria. The resulting weights were computed in Expert Choice (EC) software to determine priority weights. The sensitivity analysis was also performed for validating robustness of decision. The outcome of this research would help development ofa sustainable land suitability model for hillside development. Â© 2014 The Authors. Published by Elsevier Ltd.